Implementing Customer Relationship Management on Bisiness Startup Tanjung Florist To Increase Value, and Company's Revenue (The Indonesian Journal of Business Administration, 2015)
Abstract. Tanjung Florist is a startup business which started as a hobby and will be developed like a professional startup business. The business runs from the year of 2013 and has run for almost a year. The current concern is that the sales of Tanjung Florist has come to a stagnant position. Before taking the decision of solving the problem, the writer is analyzing the issue by analyzing the company internally using Segmentation, Targeting and Positioning (STP) and Marketing Mix, and analyzing the tangible and intangible resouces of the company. Then continued by analyzing the external environment of Tanjung Florist by using Porter’s Five Forces and PEST.Internal environment analysis is developed using Strengths and Weaknesses of Tanjung Florist, while the external environment analysis is developed using Opportunities and Threats Analysis and resulted in SWOT Analysis of Tanjung Florist. The next method is to solve the root problem that is faced by Tanjung Florist by using the Matrix TOWS method which has 4 basic strategies, they are maxi-maxi, maxi-mini, mini-maxi, dan mini-mini strategy. The most efficient strategy is by implementing mini-maxi strategy, giving a mini treatment with a maxi result, that is by putting CRM for startup business into practice. Implemented CRM is CRM adjusted to the condition of Tanjung Florist business by making use of facilities that can be acquired easy and less cost.Implementing CRM is to integrate database and make operational of the company more efficient in order to increase the service quality of the company to the customers and to cut the operational cost. Customer satisfaction becomes the main goal by implementing CRM expecting customer loyalty and lifetime value customer can be formed towards the company and in the end, implicate towards the increase of the company’s profits. On this research, the focus is to build facilities to implement CRM such as Cloud to integrate data, social media as a communication media to the customers and chat media platform to cut operational cost and increase work efficiency.The benefit resulting from implementing CRM can be seen in a long term run simultaneously with the increase of the company’s value by giving excellent service to the customers. The benefit which is aimed in implementing CRM is work efficiency and integration to get customer loyalty with the final goal is to increase the company’s profits from the customer’s repeat orders and decreasing operational cost. Keyword : Customer Relationship Management, Startup , Florist